Differential responses to breath-holding, voluntary deep breathing and hypercapnia in left and right dorsal anterior cingulate - Holton, P; Huang 黄永志, Y; Bahuri, NFA; Boccard, S; Hyam, JA; Paterson, DJ; Dorrington, KL; Aziz, TZ; Moosavi, SH; Green, AL (Wiley, 2021)
New Findings What is the central question of this study? This study investigated the role of dorsal ACC in respiration control using local field potential recordings in human ACC. What is the main finding and its importance? The results suggest that the neurophysiological responses in dorsal ACC to different breathing tasks varied and were different between left and right ACC. In addition, the differential lateralisation of the left and right ACC was demonstrated by tractography analysis. Abstract The role of subcortical structures and cerebral cortex in the maintenance of respiratory homeostasis in humans remains poorly understood. Emerging evidence suggest an important role of the anterior cingulate cortex (ACC) in respiratory control. In this study, local field potentials (LFPs) from dorsal ACC were recorded in humans through implanted deep brain electrodes during several breathing activities, including voluntary activities of breath holding and deep breathing, and involuntary activities of inspiration of varying concentrations of carbon dioxide (1%, 3%, 5% and 7%). We found that the breath holding task induced significant unilateral left‐sided ACC changes in LFP power, including an increased activity in lower frequency bands (3‐5 Hz) and decreased activity in higher frequency bands (12‐26 Hz). The respiratory task involving reflex increase in ventilation due to hypercapnia (raised inspired CO2) was associated with bilateral changes in activity of the ACC (again with increased activity in lower frequency bands and reduced activity in higher frequency bands). The voluntary breathing task with associated hypocapnia (deep breathing) induced bilateral changes in activity within low frequency bands. Furthermore, probabilistic diffusion tractography analysis showed left‐sided connection of the ACC with the insula and frontal operculum, and bilateral connections within subsections of the cingulate gyrus and the thalamus. This electrophysiological analysis provides direct evidence for a role of the ACC in respiratory control in humans.